Terpaan Media Sosial dan Pengaruhnya pada Tingkat Cyberchondria Dimediasi Rasa Takut Cacar Monyet - Maisaroh -; Dadang Rahmat Hidayat; Gema Nusantara Bakry (STARKI, 2022)
An abundance of Monkeypox’s news outbreak rapidly spread across the world, including Indonesia. Social media exposure leads to the fear of Monkeypox which then influences the cyberchondria severity in public, particularly the social media user. This study aims to determine: 1) whether there is an influence between social media exposure and cyberchondria severity; 2) if any influence between social media exposure and the fear of Monkeypox; 3) is there any influence between the fear of Monkeypox to the cyberchondria severity; and 4) how the influence of social media exposure mediated by the fear of Monkeypox increases cyberchondria severity. The research was conducted in quantitative research methods with purposive sampling by distributing online questionnaires (n = 515, G*Power = 485). The analysis of research was examined by using IBM Statistics PROCESS 4th model by Andrew F. Hayes, Cronbach’s α = .919 in total. The results show that 1) social media exposure significantly influences the cyberchondria severity; 2) There’s a significant influence between social media exposure and the fear of Monkeypox; 3) The fear of Monkeypox encourages the cyberchondria severity; 4) There is also an indirect effect from social media exposure mediated by the fear of Monkeypox to the cyberchondria severity level. Keywords: Monkeypox’s social media exposure; Cyberchondria; The fear of Monkeypox